Pengaruh Disiplin Kerja dan Fasilitas Kerja terhadap Kinerja Karyawan CV Alif Media Informatika - Pramudias Gilang Ramadhan; Udik Jatmiko; Suseno Hendratmoko (Master Manajemen, 2025)
This research aims to determine the influence of work discipline and work facilities on the performance of CV Alif Media Informatika employees. This type of research is quantitative research. This research data was obtained through primary and secondary data. The population in this study were employees at CV Alif Media Informatika. The sample in this study was 32 employees with a sampling technique using saturated sampling. The analysis techniques used are validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The research results show that the partial t test results of work discipline and work facilities variables influence the performance of CV Alif Media Informatics employees. The results of the F test simultaneously work discipline and work facilities influence the performance of CV Alif Media Informatics employees.